ChemInform Abstract: Cross‐Coupling Reactions Catalyzed by an N‐Heterocyclic Carbene—Pd(II) Complex under Aerobic and CuI‐Free Conditions. Issue 8 (February 2015) - Lu, Hongfei; Wang, Lin; Yang, Feifei; Wu, Runze; Shen, Wei
Abstract The Pd carbene complex catalyzes Sonogashira and Heck reactions in good yields.